Rhizosphere microbial community assembly and association networks strongly differ based on vegetation type at a local environment scale - Liu, Luxian; Ma, Liya; Zhu, Mengmeng; Liu, Bo; Liu, Xu; Shi, Yu (Frontiers in Microbiology, 2023)
Rhizosphere microbes perform critical functions for their hosts, and their structure is strongly influenced by vegetation type. Although studies on the effects of vegetation on rhizosphere microbial community structure have been conducted at large and global environment scales, studies at local environment scales would eliminate numerous external factors such as climate and soil type, while highlighting the potential influence of local vegetation type. Here, we compared rhizosphere microbial communities using 54 samples under three vegetation types (herb, shrubs, and arbors, with bulk soil as the control) at the campus of Henan University. 16S rRNA and ITS amplicons were sequenced using Illumina high throughput sequencing. 12,730,609 bacterial sequences and 9,153,794 fungal sequences were obtained, with 104,824 bacterial Amplicon Sequence Variants (ASVs) and 13,233 fungal ASVs observed. Rhizosphere bacterial and fungal community structures were influenced considerably by vegetation type. Bacterial alpha diversity under herbs was significantly different from that under arbors and shrubs. The abundance of phyla such as Actinobacteria was extremely higher in bulk soil than in the rhizosphere soils. Herb rhizosphere harbored more unique species than other vegetation type soils. Furthermore, microbial community assembly in bulk soil was more dominated by deterministic process, whereas the rhizosphere community assembly was dominated by stochasticity. In addition, rhizosphere microbial networks were less complex than bulk soil networks, and their keystone species differed based on vegetation type. Notably, bacterial community dissimilarities were strongly correlated with plant phylogenetic distance. Exploring rhizosphere microbial community patterns under different vegetation types could enhance our understanding of the role of rhizosphere microbes in ecosystem function and service provision, as well as basic information that could facilitate plant and microbial diversity conservation at the local environment scale.